2013
DOI: 10.1007/s11523-013-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ER, PR, HER-2, Bcl-2, p53, proliferative and apoptotic indexes with HER-2 gene amplification and TOP2A gene amplification and deletion in four molecular subtypes of breast cancer

Abstract: The aim of our study was to investigate HER-2 and TOP2A gene status and their correlation with Bcl-2, p53, Ki67, ssDNA, and clinicopathological parameters in four molecular subtypes of breast cancer. Seventy-four paraffin-embedded samples are immunohistochemically studied for the expression of estrogen receptor (ER), progesterone receptor (PR), HER-2, p53, Bcl-2, ssDNA, and Ki67, while HER-2 and TOP2A gene status by fluorescence in situ hybridization was investigated in 60 samples. Luminal A and B subtypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…To the best of our knowledge, although there is no significant difference, patients with luminal B (HER2-negative and HER2-positive) and HER2-overexpression breast cancer with BCL2 expression tend to have good prognosis. This observation is supported by the results of previous studies that showed that BCL2 is inversely correlated with proliferative markers, such as Ki-67, and HER2-overexpression, and hence plays an antiproliferative role despite its antiapoptotic effect [ 27 28 ]. In luminal B (HER2-negative) breast cancer, which expresses a high Ki-67 level (threshold ≥20%), BCL2 expression is high, but BCL2 plays an antiproliferative role, resulting in a more favorable outcome compared to that of breast cancer with BCL2-negative expression.…”
Section: Discussionsupporting
confidence: 78%
“…To the best of our knowledge, although there is no significant difference, patients with luminal B (HER2-negative and HER2-positive) and HER2-overexpression breast cancer with BCL2 expression tend to have good prognosis. This observation is supported by the results of previous studies that showed that BCL2 is inversely correlated with proliferative markers, such as Ki-67, and HER2-overexpression, and hence plays an antiproliferative role despite its antiapoptotic effect [ 27 28 ]. In luminal B (HER2-negative) breast cancer, which expresses a high Ki-67 level (threshold ≥20%), BCL2 expression is high, but BCL2 plays an antiproliferative role, resulting in a more favorable outcome compared to that of breast cancer with BCL2-negative expression.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, our study indicated that the biomarkers related to cell proliferation and transformation may be served as the potential therapeutic targets for HEBC and TNBC patients. In this study, as high as 71.7% LBC expressed Bcl-2, which was consistent with the finding from Olivera et al, whereas the expression of this biomarker was only 22% and 26% respectively in HEBC and TNBC [20]. The Bcl-2 overexpression was associated with a favorable outcome [21] and the reduction in expression of Bcl-2 protein was associated with progression and aggressive form of disease [22].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study also identified higher Ki67 expression levels in triple-negative and HER2-positive subtypes compared with the luminal subtypes (27). However, whether the levels of Ki67 are highest in the triple-negative or the HER2-positive subtype required further investigation.…”
Section: Discussionmentioning
confidence: 88%